G5.89: an explosive outflow powered by a proto-stellar merger?. (23rd April 2019) - Zapata, Luis A; Ho, Paul T P; Guzmán Ccolque, Estrella; Fernández-Lopéz, Manuel; Rodríguez, Luis F; Bally, John; Sanhueza, Patricio; Palau, Aina; Saito, Masao
ABSTRACT: The explosive outflows are a newly discovered family of molecular outflows associated with high-mass star-forming regions. Such energetic events are possibly powered by the release of gravitational energy related with the formation of a (proto)stellar merger or a close stellar binary. Here, we present sensitive and high angular resolution observations (0.85 arcsec) archival CO(J = 3–2) observations carried out with the Submillimeter Array of the high-mass star-forming region G5.89−0.39 that reveal the possible presence of an explosive outflow. We find six well-defined and narrow straight filament-like ejections pointing back approximately to the centre of an expanding molecular and ionized shell located at the centre of this region. These high-velocity (−120 to +100 km s −1 ) filaments follow a Hubble-like velocity law with the radial velocities increasing with the projected distance. The estimated kinematical age of the filaments is about of 1000 yr, a value similar to the dynamical age found for the expanding ionized shell. G5.89 is the thus the third explosive outflow reported in the galaxy (together with Orion BN-KL and DR21) and argues in favour of the idea that this is a frequent phenomenon. In particular, explosive outflows, in conjunction with runaway stars, demonstrate that dynamical interactions in such groups are very important ingredients in star formation.